Unanticipated discovery of two rare gastropod molluscs from recently located hydrothermally influenced areas in the Okinawa Trough - Chen, Chong; Watanabe, Hiromi Kayama; Miyazaki, Junichi; Kawagucci, Shinsuke (PeerJ (San Francisco, CA), 2017)
The deep-sea hydrothermal vent is one of the most 'extreme' environments in the marine realm. Few species are capable of inhabiting such ecosystems, despite extremely high productivity there supported by microbial chemosynthesis, leading to high biomass and low species richness. Although gastropod molluscs are one of the main constituents of megafaunal communities at vent ecosystems, most species belong to several typical families (e.g., Provannidae, Peltospiridae, Lepetodrilidae) specialised and adapted to life at vents. During recent surveys of Okinawa Trough hydrothermal vent systems, two snails atypical of vent ecosystems were unexpectedly found in newly discovered hydrothermally influenced areas. Shell and radular characteristics were used to identify the gastropods morphologically. One species was a vetigastropod, the calliostomatid (Sakurai, 1994); and the other was a caenogastropod, the muricid (Okutani, 1959). Both gastropods were previously only known from regular non-chemosynthetic deep-sea and very rare-only two definitive published records exist for and three for . The radula formula of is accurately reported for the first time and based on that it is returned to genus . For both species, barcode sequences of the cytochrome oxidase I (COI) gene were obtained and deposited for future references. These new records represent the second record of calliostomatids from vents (third from chemosynthetic ecosystems) and the third record of muricids from vents (tenth from chemosynthetic ecosystems), and extend the distribution of both species to the southwest. Neither family has been recorded at chemosynthetic ecosystems in the western Pacific. Both were from weakly diffuse flow areas not subject to high temperature venting but were nevertheless associated with typical vent-reliant taxa such as tubeworms and mussels. These new records show that these species are capable of tolerating environmental stress associated with weak hydrothermally influenced areas, despite not being vent endemic species, adding to the list of known vent/non-vent species intersections. This signifies that such weakly influenced areas may provide key habitats for them, and that such areas may play a role in the evolution of biological adaptations to 'extreme' chemosynthetic ecosystems.